2017
DOI: 10.1039/c7ta02151h
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the atomic structure of Li2MnO3 in Li-rich Mn-based cathode materials and the impact of its atomic arrangement on electrochemical performance

Abstract: Local heterogeneity in crystal lattice is directly observed in synthesized Li2MnO3/LiMO2 (M = Ni, Mn) cathode materials. With SAED application, for the first time, we accordingly uncover that the lattice heterogeneity is induced by different Li2MnO3 atomic arrangements coexisting in same crystal domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…However, in Li‐aluminate and Na‐aluminate coated samples, the changes in the c ‐lattice parameter are rather noticeable (≈3.7% and ≈2.7%, respectively). This observation may relate to the degree of cubic spinel phase formation [ 73 ] though further studies for revealing this observation were beyond the scope of this work. The results of the post‐cycling TEM analysis of the uncoated and coated HE‐NCM electrodes are presented in Figures and ; Figure S10, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Li‐aluminate and Na‐aluminate coated samples, the changes in the c ‐lattice parameter are rather noticeable (≈3.7% and ≈2.7%, respectively). This observation may relate to the degree of cubic spinel phase formation [ 73 ] though further studies for revealing this observation were beyond the scope of this work. The results of the post‐cycling TEM analysis of the uncoated and coated HE‐NCM electrodes are presented in Figures and ; Figure S10, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…For more detailed information on the pristine structures of both NCM [2,17,18,28,61,115,116] and HE-NCM, [34,41,48,51,112,[117][118][119][120][121][122][123][124][125] we refer to other reports available in the literature. Note that by this evaluation method, the number of subsequently stacked defect-free TM layers is determined.…”
Section: Structure Of Li-rich He-ncmmentioning
confidence: 99%
“…It is reported that Li‐rich materials are composed of two phases of Li 2 MnO 3 ( C 2/m ) and LiMO 2 (R3¯m) (M = Ni, Co, Mn, etc.) . Despite the above advantages, several concerns including structural instability and the resulted voltage degradation, as well as the poor diffusion kinetics at the interface have become the bottlenecks of Li‐rich materials …”
Section: Introductionmentioning
confidence: 99%
“…

HEVs (PHEVs), besides the traditional applications in portable devices. [5][6][7][8][9] Despite the above advantages, several concerns including structural instability and the resulted voltage degradation, as well as the poor diffusion kinetics at the interface have become the bottlenecks of Li-rich materials. [1][2][3] Lithium-rich (Li-rich) materials, with the specific capacity over 260 mAh g −1 and energy density up to ≈1000 Wh kg −1 , [4] have attracted great interest in the past decades.

…”
mentioning
confidence: 99%